Analisis Penerapan Akuntansi pada Usaha Alat Tulis Kantor di Alfapro Stationery (Jurnal Kendali Akuntansi, 2025)
This study analyzes the implementation of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) at Alfapro Stationery. The analysis results indicate that Alfapro Stationery has applied several basic principles of SAK EMKM in preparing its financial statements, such as recognizing fixed assets based on acquisition costs, recording inventory, and recognizing revenue and expenses. The financial statements prepared include the statement of financial position, income statement, and notes to the financial statements, supported by a computer-based accounting system (AIO System) that helps generate automatic financial reports every month, thereby increasing accuracy and transparency. However, Alfapro Stationery has not been able to separate personal and business assets, violating the "Separate Economic Entity" concept, which is fundamental in preparing financial statements according to SAK EMKM. Although the company's financial statements formally appear to meet the requirements of SAK EMKM, the lack of clear separation between personal and business assets indicates non-compliance with the standard. Further research can focus on a more in-depth analysis of the effectiveness of the internal control system, evaluating the impact of the latest technology on store operations, better human resource management strategies, and comparative studies with other UMKM that have best practices. This aims to provide broader perspectives and innovative solutions to be implemented at Alfapro Stationery.